68Ga CXCR-4 PET/CT Imaging in an Atypical Case of Extramedullary Plasmacytoma Mimicking as Renal Cell Carcinoma. (July 2019) - Kumar, Rajender; Mittal, Bhagwant Rai; Sood, Apurva; Singh, Harmandeep; Shukla, Jaya; Nada, Ritambra; Rathi, Manish
Abstract : Abstract: Multiple-myeloma (MM) is a malignant plasma cell proliferation disorder and the second most common blood malignancy after non-Hodgkin lymphoma. The chemokine (CXCR-4) receptor analogues are the newer agents being postulated for myeloma imaging and have shown good diagnostic performance. We report a case of plasmacytoma with suspicious renal cell carcinoma, in whom 68 Ga CXCR-4 PET/CT revealed tracer-avid lesion in the left perinephric region. PET/CT-guided biopsy from the tracer-avid lesion revealed plasmacytoma. PET/CT-imaging and guided biopsy using 68 Ga CXCR4 receptor ligand, proved its usefulness for accurate localization of the culprit lesion and helped in definitive management of the patient.